Menuju Generasi Berkarakter: Sosialisasi Pendidikan Antikorupsi di SMK Al-Falah Jakarta - Santi Rimadias; Marissa Grace Haque; Ajeng Rida Riyanti; Catur Nugrahani; Nikita Dewi Anjani Sudrajat; Putri Aisy Salma; Riedmen Gifar Widagdo; Yola Pangestu Anggraeni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Corruption remains a major challenge that hinders economic, social, and political progress. To overcome this problem in Indonesia, the STIE Indonesia Banking School community service team implemented an Anti-Corruption outreach program initiative targeted at Al-Falah Vocational School in Jakarta. This program utilizes a combination of interactive lectures, participatory discussions, and interesting quizzes to convey anti-corruption principles. The results of this program show a significant increase in students' understanding of corruption, its negative impacts, and the important role of integrity. These results underscore the efficacy of early anti-corruption education in cultivating a generation committed to ethical behavior and integrity and laying the foundation for a corruption-free future.